KAJIAN FAKTOR KENDALA SISTEM PEMBELAJARAN E-LEARNING - AMINULLAH AMINULLAH (Universitas Mahasaraswati K. Mataram, 2021)
The purpose of this study is to examine the constraint factors of the e-learning learning system. This type of research is literature review research with a descriptive approach. The results of the study obtained regarding the constraint factors in the e-learning learning system include; quota and network/internet connection, equipment used, learning facilities, understanding of course management in e-learning, limited time for managing e-learning, lack of commitment from schools and teachers regarding the development of e-learning learning, funds needed for e-learning implementation still limited, school leadership policies in allocating funds for the development of learning media, long loading times for information or films, mentoring time by parents, teachers' technological abilities, costs, psychologically face-to-face directly affect the level of understanding